A bend in the roads - Sparks, Nicholas (USA : Grand Central Pub, 1999)
Devastated by the death of his wife in a hit-and-run accident, Miles, deputy sheriff of New Bern, North Carolina, discovers new meaning in his life when he meets Sarah Andrews, a woman struggling to rebuild her own life.
Keywords: Hit-and-run drivers -- Fiction; Traffic accident victims -- Family relationships -- Fiction; New Bern (N.C.) -- Fiction; North Carolina --Fiction.